An exploratory framework of drug related crime in forensic sciences and criminology - Sujit Kumar Sarker; Faller, Erwin Martinez (Malaysian Society of Applied Biology, 2016)
Inevitably, drug and crime are correlated as a global contributor to the social problems. According to World Drug Report (2015) of the United Nations Office on Drug and Crimes (UNODC), a total of 246 million people or 1 out of 20 people between the ages of 15 and 64 years, uses illegal drugs. Goldstein’s (1985) conceptual analysis offered a tripartite classification of drugs violence connections. Goldstein’s frameworks detailed on a psycho-social opportunity of drug users to commit a crime which focuses on a psychopharmacological link, compulsive economic link and systemic link. The research objective was to identify drug related crimes in forensic sciences and criminology that may be essential for relative developmental framework. Results identified on major illegal drugs in relation to violence were cocaine, phencyclidine, lysergic acid diethylamide, methamphetamine, ecstasy, heroin, marijuana, etc. The crimes most often committed by illegal drug users were theft, burglary, robbery, prostitution, assault, rape etc. This framework cleared the importance of drug related crime. There is a need for concrete developmental agenda, integrated responses and health intervention scheme besides the law for prevention of drug related crime.